Patofisiologi Selulit - Jesryn Dhillon; Nelva Karmila Jusuf (PT Kalbe Farma Tbk., 2023)
Cellulite is a topographic change of the skin commonly found in the buttocks and thighs in the majority of post-pubertal women. Cellulite in males is usually accompanied by hormonal disorders. Histological changes were found in the dermis, adipose tissue, and septa. The pathophysiology of cellulite is yet to be determined, several factors are suspected.